FTIR spectroscopy combined with chemometric for analysis of sesame oil adulterated with corn oil - Ahmad Fadzillah, Nurrulhidayah; Che Man, Yakoob; Rohman, Abdul (Taylor & Francis, 2014)
Sesame oil is an edible vegetable oil derived from the sesame seed that has been used as a flavor enhancer in Southeast Asian cuisine. This highly valuable oil can be subjected to adulterations with lower price oils in order to gain economical profit. Among 10 vegetable oils evaluated using fatty acid profiles with principal component analysis, corn oil has the closest similarity in fatty acids combined together with sesame oil; therefore, corn oil is a potential adulterant in sesame oil. FTIR spectra at 1072−935 cm−1 was chosen for quantitative analysis with acceptable values of coefficient determination (R2), root mean square errors of calibration and prediction. These combined methods using first derivative FTIR spectra in partial least square showed well quantified corn oil in sesame oil with R2 (0.992), root mean square errors of calibration (0.53% v/v) and root mean square errors of prediction (1.31% v/v) values. Moreover, the Coomans plot based on Mahalanobis distance were able to discriminate between sesame oil with adulterated oils such as corn oil, grape seed oil, and rice bran oil.